Identifikasi Dampak Limbah Pasar Ikan Terhadap Keberlangsungan Wisata Kuliner Seafood Di Pantai Kedonganan, Bali - Ardana, Mella Amelia; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2024)
The aim of this research is to find out what waste is produced by the Kedongan Fish Market and the management carried out as well as to find out its impact on the sustainability of tourism and visits by seafood culinary tourists to Kedonganan beach. The methods used to collect data in this research were observation, interviews, document review and documentation results and literature study. The data analysis method used in writing this research report is qualitative descriptive analysis. The results of this research are that the waste produced by the fish market is in the form of liquid waste and solid waste. This waste management is carried out by the Traditional Village, but it is still not optimal due to the lack of cooperation from the traders. Meanwhile, the impact of fish market waste results in disruption of the sense of smell, because the smell is quite pungent, liquid waste in the form of discarded or leaked fish water makes the roads around the market muddy, slippery and smelly. This doesn't really affect tourist visits to Kedonganan Beach seafood culinary delights, but it is quite annoying for tourists. All parties who manage fish markets and culinary tourism should synergize well, so that in the future seafood culinary tourism and the Kedonganan Fish Market can develop better and be more hygienic. Keywords: culinary tourism, fish market, waste